PIK3CA in Colorectal Cancer - Cathomas, Gieri (Frontiers in Oncology, 2014)
PIK3CA, the catalytic subunit of PI3K, is mutated in many different tumours, including colorectal cancer. Mutations of PIK3CA have been reported in 10 – 20% of colorectal cancer, about 80% of mutations found in two hot spots in exon 9 and exon 20. In RAS wild-type colorectal cancers, PIK3CA mutations have been associated with a worse clinical outcome and with a negative prediction of a response to targeted therapy by anti-EGFR monoclonal antibodies. However, these findings have not been confirmed in all studies and subsequent more detailed analysis has revealed that these effects may be restricted to mutations in Exon 20. Finally, mutations in PIK3CA may be the long sought biomarker for successful adjuvant therapy with aspirin in patients with colorectal cancer. Therefore, PIK3CA mutations appear to be a promising predictive biomarker; however, further data are needed to conclusively define the impact of somatic mutations in the PIK3CA gene for the management of patients with colorectal cancer.